Toda saudade é uma espécie de velhice - Ferreira, Ana Luiza Guedes (Universidade Federal de São Carlos, 2022)
This conclusion work was to highlight in the narratives shared by elderly people who describe about their life stories and their relationship with aging process. In addition, identify and resonate, which narrates the voice of the old man. Using qualitative analysis, a technical organization was carried out in subsets, separated by subjects, seeking to portray the meanings expressed by the interviewees. The themes chosen were: the becoming of those who age, the narrative as a human activity, the memory for those who narrate and the retelling of Time. I hope that this work, like the Museu da Pessoa, moves towards housing the uninhabitable, in opposition to what passive social life predicts, and gives visibility and listening to the substance of life that vivifies the elderly: the living past.
All nostalgia is a kind of old age
Keywords: Terapia ocupacional; Histórias de vida; Velhice; Museu da pessoa; Memória; Occupational therapy; Life stories; Old age; Memory; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL